Achieving 435-2540 Tonnes Per Shift from Continuous Miner Sections, A Report on the USAÆs Most Productive Coal Mines - Volkwein J. C; Kissell F. N (The Australasian Institute of Mining and Metallurgy, 1988)
The U.S. Department of Interior's Bureau of Mines has the opportunity to visit many U.S. mines, including some that claim 2 to 5 times the national average of 334 raw tonnes/unit shift (tps) from a continuous miner section. In a project to assess the reasons for this high production, the Bureau conducted two studies. The first study focused on the 25 highest producing continuous miner sections. What stood out during the visits-was the quality of the labor-management relations. In each of the mines there was a positive labor/management relationship based on mutual trust and a sense that the employees were the company's most valuable resource. Discussions with labor revealed a universally positive attitude toward the company. Interviews with the mine superintendents invariably ranked the quality and attitude of workers as more important than anything else. Also during the mine visits of the 25- mine study, no engineering factors obviously stood out. Time at the face was greater than average, most were in coal over 1.52 m and the roof was generally good. Also, none of the 25 mines had to contend with high methane levels. Because this study found that a high percentage of mines were in seams less than 1.52 m thick, the second study examined thin seam mines only.